1994
DOI: 10.2307/2951664
|View full text |Cite
|
Sign up to set email alerts
|

Switching Costs and the Gittins Index

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.This content downloaded from 131.215.70.231 on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 6 publications
3
79
0
Order By: Relevance
“…Ainslie 1975). Additionally, if there is a cost associated with switching from one behaviour to another, then not only is the Gittins index no longer optimal, but also there is no optimal index that may be calculated independently for each bandit (Banks & Sundaram 1994). It is well recognized that, under many conditions, humans exhibit costs when switching from one task to another (e.g.…”
Section: Optimal Performance In Stationary Environments: the Gittins mentioning
confidence: 99%
See 1 more Smart Citation
“…Ainslie 1975). Additionally, if there is a cost associated with switching from one behaviour to another, then not only is the Gittins index no longer optimal, but also there is no optimal index that may be calculated independently for each bandit (Banks & Sundaram 1994). It is well recognized that, under many conditions, humans exhibit costs when switching from one task to another (e.g.…”
Section: Optimal Performance In Stationary Environments: the Gittins mentioning
confidence: 99%
“…the pay-off structure of the environment must be stationary), all options must be available at all decision points (i.e. there cannot be any 'side paths') and agents must discount the value of rewards exponentially into the future (Gittins 1979;Berry & Fristedt 1985;Banks & Sundaram 1994). Real-world problems typically violate one or more of these assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Mobility costs impact the wage that will be accepted in the new city, which in turn impacts future wage growth prospects in this new city; this difference in terms of option value will have an additional impact on indifference wages, and so forth. As shown in Equation 7, this dynamic feedback 24 See, for instance, the impossibility result of Banks & Sundaram (1994).…”
Section: Proposition 1 Optimal Strategiesmentioning
confidence: 99%
“…First, Banks and Sundaram (1994) argued that any bandit problem where there are both costs of switching "away from" and "to" an arm is equivalent to another bandit problem where there is only the cost of switching to. Hence for simplicity, assume that there is only cost of switching to.…”
Section: Switching Costsmentioning
confidence: 99%
“…Banks and Sundaram (1994) showed that no index policy is optimal when switching between arms incurs costs. This survey will first discuss the properties of the bandit problem that make the Gittins index policy optimal, and show how these properties break down upon the introduction of costs on switching arms.…”
Section: Introductionmentioning
confidence: 99%